Definición de semiproductos escalares útiles en análisis de datos - Trejos-Zelaya, Javier (2004)
We develop the theory necessary for Data Analysis with inner semiproducts, extending tha classical concepts of inner products usually employed. For this, we use the basic algebraic definitions of non degenerated bilinear forms and develop all the algebraic tools needed. We study the most important operators on the individual space, such as the VM and the MV operators. We also study the case of the inner semiproduct of weights in the variable space, which corresponds to the introduction of supplementary individuals in the case of null weights. Finally, we arrive to the usual concepts of Principal Component Analysis.